Circulating Biomarkers and MicroRNAs in the Diagnosis, Prognosis and Treatment of Diabetic Cardiomyopathy-A Review - S, Moorthy; T, Koshy; SrinivasanV; S, Silambanan (Cardiology and Cardiovascular Medicine, 2020)
Background: In the year 2015, diabetes mellitus resulted in 5 million deaths which were predicted to increase by 34% in 2030. The prevalence of cardiomyopathy in diabetics is 12% and is almost 22% in people over 64 years of age. Individuals with diabetes mellitus present with cardiomyopathy in the absence of hypertension, coronary artery disease, or valvular heart disease. Diabetic cardiomyopathy is a cardiac condition presenting with heart failure characterized by diastolic dysfunction and cardiac remodeling, in the absence of signs of coronary artery disease and hypertension. Glucotoxicity and lipotoxicity are the initiators of excessive autophagy, apoptosis, altered excitation contraction coupling and remodeling of extracellular matrix with excessive fibrosis in the myocardium. Since the condition is silent during early stage, use of novel biomarkers may be useful to identify patients who are at risk of cardiomyopathy. So far, only a few studies have explored miRNAs profile in patients with diabetic cardiomyopathy with inconsistent results. Biomarkers and microRNAs have been identified to diagnostic as well as prognostic indicators of the various stages of progression of diabetic cardiomyopathy. Cardiac microRNAs target mitochondrial dysfunction and free radical production thus they have a promising role in implementing targeted therapy in patients with diabetic cardiomyopathy. This review was undertaken to understand the roles played by various biomarkers and microRNAs in the diagnosis and prognosis and therapy in patients with diabetic cardiomyopathy. Methodology: A literature search was done in PubMed, Embase, Cochrane Library, Pubmed Central, UpToDate, with the focus on biomarkers in Diabetic Cardiomyopathy. The articles selected included those on pathogenesis of diabetic cardiomyopathy, various diagnostic modes, the role played by biomarkers and miRNAs in the diagnosis especially